Reforming the Parliamentary Threshold in Indonesia's General Elections: A Legal and Fiqh Siyasah Dusturiyah Perspective - Barqi, Suha Yusbairoh; al Arif, M. Yasin; Irwantoni, Irwantoni (As-Siyasi: Journal of Constitutional Law, 2024)
This study examines the issues surrounding the establishment of the parliamentary threshold in Indonesian elections from 2009 to 2024, as well as the urgency of its reform, from the perspective of fiqh siyasah dusturiyah. The study aims to analyze the impact of the parliamentary threshold on the multi-party system and the stability of democracy and to offer solutions based on Islamic legal studies. The research employs a juridical-normative method with both a legislative and conceptual approach. Data were collected through literature studies, including legal documents, scholarly journals, and court proceedings. The study results show that applying the 4% parliamentary threshold in Law No. 7 of 2017 has led to negative consequences, such as the significant waste of valid votes and the limited access of smaller parties to the Parliament. From the perspective of fiqh siyasah dusturiyah, this policy does not fully align with the principle of maslahat, as it creates imbalances in political representation. Therefore, a threshold revision to a more rational figure, such as 1%, is needed to minimize wasted votes and reinforce the principle of democratic justice. The conclusion emphasizes that the threshold size must consider the maslahat (benefit) of society and align with the principles of fiqh siyasah dusturiyah to support implementing a more inclusive and just electoral system.